Pojęcie stosownego wynagrodzenia, o którym mowa w art. 79 ust. 1 pkt 3 lit. b ustawy o prawie autorskim i prawach pokrewnych, a jego rynkowy charakter - Maryniak, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article its author tries to find a proper definition of “respective remuneration” referred to in article 79 paragraph 1 of Polish Copyright Law (Act of 4 February 1994 on Copyright and Related Rights). Although, prima facie, in the case law this term is understood uniformly, while analysing in detail the different cases of copyright infringement it is noticeable that the judgments are based on various factors, which eventually influence the final amount of remuneration defendant must pay. These factors are usually objective (such as prices for a copy of work) but sometimes they might be also subjective (for instance: the relations between defendant and author, the motives of defendants infringement, etc.). The author of this article answers the question whether the term “respective remuneration” means the same as “market remuneration” (market prices) and proposes the original method of calculating a respective remuneration referred to in article 79 of Polish Copyright Law, called “objective-subjective method”.